Penalaran Hukum Islam: Upaya Mensinergikan Al-Aslu dan Al-Far’u - Shofiyulloh shofiyulloh (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2019)
Differences in understanding of Islamic law make Muslims divided. Some implement their understanding in a rigid, even radical form. There are also those who apply their views in a free, even liberal, form. However, what stands out is some who affirm their views in a moderate form. The dynamism of understanding in interpreting religious texts results in these three groupings of views always at any time, place, situation and condition. if traced critically, it actually comes from a less than proportional understanding of their own. They, in general, can not choose which problems are included in the space al-aslu (main) or in other expressions known as as-sawa>bit (something that is fixed, continuous and unchanging) and which problems are enter in al-far'u (branch) space or in another expression known as al-mutaghayyira>t (something that can change). Both of these spaces are an absolute requirement to be understood by interpreters of Islamic law in carrying out legal responsibilities responsibly. With this principle, in various cases, Muslims can choose and sort out, which then needs to be renewed for a more comprehensive benefit and which need not be updated as a Shari'a provision.